2017
DOI: 10.1088/1361-6528/aa5d73
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of interface exchange magnetism in self-assembled cobalt-fullerene nanocomposites exposed to air

Abstract: We report on the establishing of an exclusive magnetic effect in air-exposed CoC nanocomposites (x > 2) created through self-assembling in the depositing mixture. In order to verify the influence of ambient air on the CoC mixture film, we have studied in detail the film magnetization at rather low temperatures, which provides their ferromagnetic behavior. Tracing the possible exchange bias effect, we distinguished a clear vertical shift of the hysteresis loops recorded for the air-exposed CoC films in the fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…To prove this hypothesis, first, we analysed the optical spectra of the pure C 60 film with the same history. We also assumed that in the case of the mixture films with x > 2, the absorbed oxygen exists in the bound state as a part of the CoO phase in the Co/CoO core shell nanoparticles [23][24][25] that also excludes significant effect of the air exposure on the C 60 -based structures. Taking into account the mentioned above, we will describe our samples by the formula Co x C 60 , i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prove this hypothesis, first, we analysed the optical spectra of the pure C 60 film with the same history. We also assumed that in the case of the mixture films with x > 2, the absorbed oxygen exists in the bound state as a part of the CoO phase in the Co/CoO core shell nanoparticles [23][24][25] that also excludes significant effect of the air exposure on the C 60 -based structures. Taking into account the mentioned above, we will describe our samples by the formula Co x C 60 , i.e.…”
Section: Resultsmentioning
confidence: 99%
“…x > 2), the width of the A peak (related to the LUMO + 1-derived band) changes only slightly. It can be seen (figure 5(b)) that the widths of the C and D peaks explicitly increase with x for x > 4 where the Co clustering is significant [24,25]. This enhanced broadening of the peaks can hardly be referred to the direct interaction of C 60 with the Co cluster surface because the surface of the Co clusters is oxidized [23][24][25].…”
Section: Optical Absorption In the Co X C 60 Films: Uv-visible Rangementioning
confidence: 98%
“…An induced magnetic moment of ≈1.5-3.0 µ B was observed in a 2 nm thin layer of C 60 fullerenes from the Fe-C 60 interface. Lavrentiev et al [212] have examined magnetic properties of the nanocomposites of Co x C 60 and air-exposed samples. The hysteresis loop of the field cooling regime in the air-exposed samples shows a prominent vertical shift, which is attributed to the interface exchange magnetism at the Co/C 60 interface.…”
Section: Magnetic Studiesmentioning
confidence: 99%
“…Furthermore, it is one of the elemental forms of carbon which has great potential for being a high‐capacity hydrogen‐storage material, and possible catalyst for hydrogenation reactions with special catalytic activity due to its unique molecular structure . In addition, C 60 molecules can act as a support for metal nanoparticles (NPs) through stronger metal–π interactions and collaborate with NPs to synergistically improve catalytical activity . Zheng Xu et al.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] In addition, C 60 molecules can act as a support for metaln anoparticles (NPs) through stronger metalp interactions and collaborate with NPs to synergistically improve catalytical activity. [5][6][7][8][9][10][11] Zheng Xu et al demonstrated that C 60 can activate molecular hydrogen and is an ovel non-metal hydrogenation catalyst. [8] The hydrogenation of aromatic nitro compounds to amino aromatics was achieved with this catalyst with high yield and selectivity under 1a tmosphere of H 2 and light irradiation at room temperature.M etal complexes C 60 Pt n [9] and C 60 Pd n [10,11] have been reported to show good catalytic activity in the hydrogenation reaction of acetylene derivatives such as diphenylacetylene and nitro compoundsi nm ild reaction conditions.…”
mentioning
confidence: 99%